A Matter of Principles: Empirical Treatments of Translation Principles – A Case Study - Zhong, Yong (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractIn this paper, the author will discuss findings of an investigation into the real life experiences of 21 trainee translators with two types of translation principles, one that is biased towards the source text and its author and the other biased towards the translation and the translator. The investigation centred on the translators’ preferences of principles, rationalization of their preferences, their difficulty in tackling the principles via a translation task and their strategies for coping with the difficulties. The author believes that this investigation is the first of its kind in translation studies as it examines practitioners of principles rather than the principles themselves and, therefore, it warrants special attention.Readers will find in this paper summary discussions about research design, research methodology, a brief quantitative analysis, detailed qualititative analyses and a case study.